Production of Conjugated Linoleic Acid by Microwave‐Assisted and Ultrasound‐Assisted Alkali Isomerization: Effects of Microwave Power and Ultrasound Amplitude. (28th May 2019) - Alaşalvar, Hamza; Erinç, Hakan; Salur, Fatma; Özbey, Ayşe
Abstract: Conjugated linoleic acid (CLA) is commercially produced by alkali isomerization of linoleic acid (LNA). However, this method constitutes a relatively high content of undesirable CLA isomers. In present study, microwave‐assisted and ultrasound‐assisted alkali isomerization techniques were applied for production of CLA as an alternative to traditional alkali isomerization. This study was aimed to evaluate the isomerization degree of LNA, by using various process conditions such as microwave power, ultrasound amplitude, and their reaction times. The best conditions for LNA isomerization were a microwave power of 700 W and a reaction time of 6 h for microwave‐assisted alkali isomerization and an ultrasound amplitude of 100% and a reaction time of 6 h for ultrasound‐assisted alkali isomerization. Under determined conditions, microwave‐assisted alkali isomerization (97.21%) resulted in a higher isomerization degree compared to ultrasound‐assisted alkali isomerization (76.98%) while the content of undesirable CLA isomers in ultrasound‐assisted alkali isomerization (0.62%) was lower than that of microwave‐assisted alkali isomerization (1.87%). This study showed that application of the both techniques resulted in equal amounts of desirable CLA isomers. The content of desirable CLA isomers was 47.09% cis ‐9, trans ‐11 and 48.25% trans ‐10, cis ‐12 for microwave‐assisted alkali isomerization and 36.34% cis ‐9, trans ‐11 and 40.02% trans ‐10, cis ‐12 for ultrasound‐assisted alkali isomerization.